Penerapan Denda Keterlambatan Angsuran Pada Produk Pembiayaan Syariah (Studi Kasus Pada PT. BPRS Dana Moneter Cab. Kota Palopo, Sulawesi-Selatan) - Fachrurrazy, Muhammad; Ayyubi, H. Mukhtaram; Savitri, Dewi (Fakultas Syariah IAIN Kerinci, 2023)
This research aims to provide an overview of the application of fines for late payment of financing instalments. how to apply fines for late payment of sharia financing installments from the description of existing cases and the effectiveness of Sharia Economic Law on its application. fines imposed by Financial Institutions (PT. DANA MONETER BPRS Cab. Palopo). The method used in this research is a qualitative descriptive data analysis method. The type and approach is empirical and the case study approach is to see how the law works (juridical empirical). Secondary data reports, several financing financial reports are used as data material in this research. collecting information from research informants, namely the BPRS Monetary Fund, using observation, interviews and documentation. The research results show that: the practice of applying mulct/fines to debtors who experience delays in paying financing installments at PT. The BPRS Palopo Branch Monetary Fund is. The results obtained by field researchers and informants were that the application of fines gave consumers who could afford it but deliberately delayed payments, but in fact PT. The BPRS Monetary Fund does not include additional customer installment fees, because the fines referred to here are only used as a warning DSN-MUI fatwa (number 17/DSN-MUI/IX/2000). Regarding the permissibility of fines, the Bank has strengthened the method of applying fines to customers. Sharia Economic Law perspective on the application of fines to PT. The BPRS Monetary Fund is based on the provisions of the Sharia Economic Law Collection (KHES) regarding sanctions against someone who breaks a promise, and because of his mistakes (articles 36 and 38) the sharia economic compilation mulct application is only aimed at customers. who have problems or are able to pay but deliberately delay payment..